FTO effects the proliferation, invasion, and glycolytic metabolism of colon cancer by regulating PKM2 - Kongyan Zhang; Fei Zhang; Jiahe Wang (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Colorectal cancer (CRC) is a leading cause of cancer-related mortality worldwide. The Fat mass and obesity-associated protein (FTO), a genetic variant associated with obesity, significantly impact the energetic metabolism of mechanical tumors. However, research on the function of FTO in CRC is scarce. Methods Bioinformatics analysis of TCGA and UALCAN databases was conducted to examine FTO expression in CRC. Immunohistochemistry was used to assess FTO and PKM2 protein expression in clinical specimens. In vitro experiments utilized five human colon cancer cell lines and a normal colon epithelial cell line, with Western blotting and RT-PCR for protein and mRNA quantification, respectively, and lentiviral transfection to modulate FTO expression. Cellular behaviors such as proliferation, migration, invasion, and apoptosis were evaluated using various assays. Immunofluorescence and Seahorse Xfe96 metabolic analysis were employed to study PKM2 expression changes and glycolytic stress. The effects of PKM2 inhibition by shikonin on cell viability and glycolytic activity were assessed using CCK-8 assay and Seahorse analysis. Results An upregulation of FTO was observed in colon cancer through data mining and analysis of pathological specimens. Besides, we discovered that the impact of FTO on colon cancer glycolysis has significant implications for colon proliferation, invasion, and metastasis. The protein expression of PKM2 and the intensity of fluorescence staining in the nucleus of PKM2 were detected to be increased in colon carcinoma cells with over-expression of FTO. Conclusion FTO plays a significant role in CRC progression by regulating PKM2 and promoting glycolysis.